Utilização do gesso para fabricação de artefatos alternativos, no contexto de produção mais limpa - Munhoz, Fabiana Costa [UNESP] (2008)
In Brazil, the activities of civil construction are an issue of great concern to the environmental leaders, particularly in relation to the generation and management of the construction wastes. Given the need for sustainable development in this sector, technological innovation has become an important tool for the mitigation of environment impacts. Based on the principles of cleaner production (P + L), the aim of this work was to collaborate to the develoment of technological innovation in civil construction, aiming to reduce the waste generated in constructions. Plaster, water and polymers were used as raw materials. In order to improve the properties of the mixture, both in early age and hardened gypsum pastes, this study assessed whether an alternation in the misture proportion would yield a reduction in the absorption rate and an increase in the compression resistance, with consequent expansion of its use as an alternative material in civil construction in the production of modular panels to seal. Different types and quantities of resins were added in the water before mixing with the plaster. Laborstory tests were carried out to determine the workability of the gypsum paste, the initial and final setting time values, the absorption rate and compression resistance. Using the scanning electron microscopy, it was possible to analyze the microstructure of gypsum paste and comfirm the data obtained in laboratory tests of absorption and compression resistance. Two mixtures with additives were more relevant to the proposed objectives for this work. The results indicated that the addition of silicone, which is a commercial product, provided a decrease in the plaster absortion rate of 75%, when compared to mixture without silicone. However, their addition reduced the compression resistance of the material. The combined addition of silicone and Glenium 3200 HES yielded a reduction in water/plaster ratio of 30%, increasing the compression resistance ...